Software quality assurance - e-commerce customers satisfaction in requirements engineering process - Wan Ab. Rahman, Wan Nurhayati; Badrul Kamal, Asma’; Talha, Hazliana; Josiah, Bunjo; Adamu, Lawal; Liming, Wu; Mohd Rosli, Nur Sakinah (Science and Engineering Research Support Society, 2015)
In the requirement analysis phase, good quality requirements are needed to develop the foundation of good quality software. This paper proposes quality attributes from the SQA activities in requirement phase from the end users’ perspective in an e-commerce application.By analyzing SQA activities in requirement engineering process, we found out five quality attributes that most affect customer’s satisfaction: functionality, security, usability, reliability and efficiency. This paper describes the quality attributes that are gained from the requirements elicitation, requirements documentation, requirements validation, negotiation and the requirements management planning activities. The results show that functionality, security, usability, reliability and efficiency affect e-commerce customers’ satisfaction. Most of the online shopping websites comply with customer requirement and requirement expectations.